Workshop Pembuatan PPT Interaktif Menggunakan Aplikasi Canva di UPTD SDN Pangeranan 1 Bangkalan - Abdussalam, Abdussalam; Pratiwi, Siska; Hariyani, Yunita; Firmansyah, Ihwan (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2022)
Microsoft office powerpoint provides slide facilities to accommodate talking points that will be conveyed to students. With animation facilities, each slide can be modified very attractively. Likewise with the facilities: front picture, sound, and visual effects that can be used to make good and attractive slides so as to accommodate the learning modalities of students. This program can accommodate students who have audio, visual and kinesthetic types. Canva is an online design program that provides a variety of tools such as presentations, resumes, posters, pamphlets, brochures, graphics, infographics, banners, bookmarks, bulletins, and so on that are provided in the Canva application. The purpose of this service is a workshop on making interactive ppt using the Canva application. This workshop was conducted for UPTD SDN Pangeranan 1 Bangkalan educators. Community service activities are carried out through several stages of activities, including: Preparation and Briefing, Implementation, and Program Sustainability Planning. After the workshop, educators are able to create interactive PPT using the Canva application that is interesting and fun for students.